Effectiveness of a novel amine + zinc + fluoride toothpaste in reducing plaque and gingivitis: results of a six-month randomized controlled trial - Dutmanee Seriwatanachai; Terdphong Triratana; Petcharat Kraivaphan; Norbert Huber; Tilo Poth; Luis R. Mateo; Melissa Stellitano; Yun-Po Zhang (BMC Oral Health)
Abstract Objectives To evaluate the efficacy of a toothpaste containing amine compound, 0.5% zinc lactate, and 1400 ppm F (NaF) in comparison to a regular fluoride toothpaste containing 1450 ppm F as MFP/NaF (negative control). Plaque and gingivitis indices were determined over a 6-month period. Materials and methods In a randomized, double-blind, two-cell, parallel-group design on healthy adults from the Bangkok, Thailand area presenting with initial gingivitis (Löe-Silness gingival index ≥ 1) and visible plaque (Turesky Modification-Quigley-Hein index ≥ 1.5) were assigned test and negative control toothpastes and instructed to brush twice daily for two minutes. Results Site-level (N = 10,778) and subject-level (N = 92) data indicated that the test toothpaste increased the number of healthy sites and improved gum health as compared to the negative control toothpaste. For the test group, after 6 months, the average reduction for plaque, gingival index, and gingival severity was 31.2%, 32.3%, and 49.3%, respectively. Average reductions were greater in the test group than the negative control group across all measures. Conclusions The amine + zinc + fluoride toothpaste significantly improved measures of plaque (12× more effective) and gingivitis (5× more effective) in comparison to a standard fluoride toothpaste, suggesting that the novel formulation with antibacterial active ingredients amine and zinc facilitates more effective plaque removal, and promotes gingival health. Clinical relevance These results suggest that daily use of amine + zinc + fluoride toothpaste can provide a significant improvement in managing plaque accumulation and bleeding associated with gingival inflammation especially for patients experiencing gingivitis. Clinical trial registration NCT06563518 (registration date: August 19, 2024).